2020
DOI: 10.1111/mec.15399
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific telomere length and dynamics in relation to age and reproductive success in Cory’s shearwaters

Abstract: Individuals in free-living animal populations generally differ substantially in reproductive success, lifespan and other fitness-related traits, but the molecular mechanisms underlying this variation are poorly understood. Telomere length and dynamics are candidate traits explaining this variation, as long telomeres predict a higher survival probability and telomere loss has been shown to reflect experienced "life stress." However, telomere dynamics among very long-lived species are unresolved.Additionally, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 95 publications
4
32
0
Order By: Relevance
“…Few studies have examined whether the relationships between telomeres and reproductive success differ between the sexes. Consistent with our results, a recent study in Cory's shearwaters (Calonectris borealis), reported that females with longer telomeres in adulthood produced more offspring, while the opposite was true in males [51], but it is unclear how telomeres and longevity or lifetime fitness are related in this species or whether this results from early-life events as suggested here, or from processes that act only in adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have examined whether the relationships between telomeres and reproductive success differ between the sexes. Consistent with our results, a recent study in Cory's shearwaters (Calonectris borealis), reported that females with longer telomeres in adulthood produced more offspring, while the opposite was true in males [51], but it is unclear how telomeres and longevity or lifetime fitness are related in this species or whether this results from early-life events as suggested here, or from processes that act only in adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that R. aegyptiacus females have longer rTL across all tissues than males, corresponding to results found in previous studies across different study systems (Barrett & Richardson, 2011; Bauch et al., 2020; Rollings et al., 2017; Watson et al., 2017). It is likely that differing life histories between males and females play a part in their differing TLs (Kotrschal et al., 2007; Rollings et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The primary explanation for these observations is that somatic maintenance is prioritised in K-strategists as future survival and reproductive potential are favoured over current reproductive output (Stearns 1992). Analysis of telomere shortening, a biomarker for ageing, within the same experimental set-up also support these observations as manipulated reproductive effort had no significant impact on telomere length from 1 year to the next (Bauch et al 2020). The cost for self-maintenance appears to be paid by delaying arrival date, as reflected by the earlier arrival of males whose reproductive effort was experimentally reduced, irrespective of migratory strategy.…”
Section: Life History and Carry-over Effects From Reproductionmentioning
confidence: 56%